Espresso in taverns and other dilemmas - Bukvić, Dimitrije (Sociološki pregled, 2017)
Book review: Dragoljub B. Đorđević, The Culture of Tavern in the Mirror of Newspapers, Beograd, Službeni glasnik, 2016, 122 pp